EVALUASI LAHAN UNTUK TANAMAN PADI SAWAH SECARA PARAMETRIK DI DUSUN MOLILIULO DESA TANGGA BARITO, KECAMATAN DULUPI, KABUPATEN BOALEMO - Pakaya, Moh. Reynaldi; Nurdin, Nurdin; Dunggio, Iswan; Rahman, Rival (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
The process of evaluating land's suitability for a particular use, such as finding prospective new land for rice field is known as land evaluation. The purpose of this study was to determine the characteristics, the quality, and the suitability of land parametrically for the development of rice field. This research took place in Moliliulo, Tangga Barito Village, Dulupi District, Boalemo Regency, from March to August 2022. This research used a detailed level survey method where the variables observed were land characteristics in the form of physical properties, and then the chemical properties were analyzed in the laboratory. Furthermore, an analysis of the characteristics and suitability of land for rice field was carried out using a parametric approach. The results of this study indicated that the characteristics and quality of the land in the study area varied greatly from low to high category, starting from climate, land, and soil nutrient availability factors. The research location has 4 land suitability classes for rice field (Oryza sativa L.), namely class 1 (excellent) with an area of 17.52 ha (2.15%), class 2 (good) with an area of 3.08 ha (0. 38%), class 3 (sufficient) with an area of 710.44 ha (87.15%), and class 4 (poor) with an area of 58.15 ha (7.13%).